Instrumentalizing Antisemitism: Review of The Politics of Unreason - Ido de Haan (University of Groningen Press, 2021)
Review of Lars Rensmann. 2017. The Politics of Unreason. The Frankfurt School and the Origins of Modern Antisemitism. Albany: State University of New York Press.